The task and future of New Testament Studies - Breytenbach, Cilliers (HTS teologiese studies, 2023)
In the light of various new tendencies in New Testament Studies, this article charts out the task for future students and researchers in the field. Within the frame of newer socio-cognitive discourse studies, it builds on the semiotic foundation that controlled interpretation of the ancient Greek text as a complex sign-system enabling the community of professional readers to construct meaning fitting the text. Such interpretations need to simulate the interpretation process within the original epistemic community. The article aims to reassess the role of exegesis in Testament Studies and a redesign of its sub-disciplines.Contribution: The article makes an original contribution to realign the hermeneutical task to interpret the text in the New Testament with socio-cognitive discourse studies. It follows trends in reception studies in distinguishing semantic interpretation from the various uses of such consensual text and conforms to interpretation of the New Testament in the realm of faculties of theology and within academic and public discourse.